Usulan Standar Tingkat Pencapaian Perkembangan Anak Usia 0-1 Tahun - Palupi, Diana Indah; Lesmana, Diana Earlyana; Farista, Dian; Yusnita, Erlin; Rahmani, Emma; Gustina, Hera; Pertiwi, Hikmah; Susanti, Debie (EDUKASIA Jurnal Pendidikan dan Pembelajaran, 2023)
This article discusses the process of growth and development of children aged 0-1 years which is continuous throughout the stages of life, but the speed of growth varies according to the stages of age. Growth is a change in the number, size, size of the body or limbs, which can be physically measured through weighing, measuring height, measuring head circumference, arm circumference and others. Development is the increase in abilities or skills in more complex body structures and functions in a regular and predictable pattern as a result of experience and the process of movement, intellectual, social and emotional maturation. Development is influenced by heredity, environment, culture and family values in each individual. The combination of these factors gives rise to the wide variety of variations that can be observed in children. Growth and development occur very rapidly, therefore stimulation of children at this age is very important because healthy and intelligent children will grow and develop optimally. The rate of growth and development of children aged 0-1 years which is described in various sources and guidelines in the national curriculum, there are proposed indicators of development in aspects of language development, namely the ability to express language and listen through non-verbal communication through children's reading books.